Numerical Solutions of Micropolar Nanofluid over an Inclined Surface Using Keller Box Analysis - Rafique, Khuram; Alotaibi, Hammad; Nofal, Taher A.; Anwar, Muhammad Imran; Misiran, Masnita; Khan, Ilyas (Hindawi, 2020)
The Brownian motion and thermophoretic impacts attained a noticeable intention of the recent researchers because these factors trigger the thermal conductivity of the nanofluid. In this study, we focus on radiation and Soret effects on a slanted stretchable sheet. Buongiorno’s model is taken into account with Brownian motion and thermophoretic effects. Compatible transformations are implemented to attain the nonlinear differential equation from the boundary value PDE’s. the physical quantities of practical interest are treated by graphically as well as numerically. For numerical results, the Keller box technique is applied. the numerical outcomes through tabulated magnitudes performed a good settlement with already existing results. Energy transfer rate against involved factor exhibited via graphs. Energy and mass transport rates enhance against increment in Soret factor while skin friction diminishes. Moreover, Nusselt number and Sherwood number decrease on improving inclination while skin friction increases